2020
DOI: 10.1136/bcr-2019-231524
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica spectrum disorder and active tuberculosis

Abstract: Tuberculosis is on the rise again. It brings with it potential for neurological involvement both as a direct infection and as a parainfectious process. Accordingly we report the development of neurological problems affecting a 48-year-old patient’s vision and sensation while being treated for active tuberculosis. At its nadir her vision deteriorated to nil perception of light and she had a sensory level to T10. Neuromyelitis optica spectrum disorder was diagnosed. We discuss our management strategy with neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In one case, a patient in the initial phase of her TB therapy had an NMO relapse which was treated with IVMP followed by oral prednisolone. 5 Luckily this patient did not have reactivation. Steroids have also been used for NMOSD in the setting of chronic HBV as well.…”
Section: Discussionmentioning
confidence: 78%
“…In one case, a patient in the initial phase of her TB therapy had an NMO relapse which was treated with IVMP followed by oral prednisolone. 5 Luckily this patient did not have reactivation. Steroids have also been used for NMOSD in the setting of chronic HBV as well.…”
Section: Discussionmentioning
confidence: 78%
“…Just in South Africa, a higher proportion 6 of active pulmonary tuberculosis in NMO patients compared with healthy controls has been described (79% vs. 14%, P = 0.0013 < 0.05) [ 42 ]. This has been reported in different populations across the world [ 42 , 43 , 44 , 45 , 46 , 47 ]. Our phylogenetic analysis showed that aquaporin from Mycobacterium sp .…”
Section: Finding the Genesis: Cross Reactivity And Molecular Mimicry ...mentioning
confidence: 54%
“…Recently, a case of NMOSD manifesting during the initial phase of AT in a female patient was treated with rituximab in cyclic infusions with a favorable outcome [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the discovery of anti-AQP4ab, a small number of reports, involving diagnoses of concomitant [ 5 , 9 , 10 ] or associated [ 4 , 11 , 12 ] NMOSD and pulmonary tuberculosis (PT) have been published. For associated NMOSD and PT, the neurological symptoms attributed to both the central nervous system (CNS) due to NMOSD and to PT dissemination into CNS defined the conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation